OC-025 STRATEGY FOR SURGICAL TREATMENT OF GIANT INGUINOSCROTAL HERNIA - SERIES OF 21 CONSECUTIVE PATIENTS DURING 15 YEARS. (13th October 2022) - Zuvela, M; Galun, D; Bogdanovic, A; Palibrk, I; Velickovic, J; Djukanovic, M; Zivanovic, M; Zuvela, M; Zuvela, M
Abstract: Aim: To present our strategy for surgical treatment of patients with giant inguinoscrotal hernia whose hernia defect is ≥10 cm or who have a loss of domain. Material and methods: Between January 2006 - January 2022, 21 consecutive patients with giant inguinoscrotal hernia and high risk of postoperative intra-abdominal hypertension were managed. The hernia was repaired in the following manner: modified Rives technique performed through direct inguinal approach in 10 patients; additional procedures were needed to reduce the volume of organs returned to the abdomen in four patients; the primary abdominal cavity was enlarged by various components separation techniques with or without mesh hernioplasty in seven patients. Results: The hernia defect size was in range 7–17 cm. In three patients the contents of the hernia sac accounted for more than 50% of the intestines: entire large bowel without the rectum, ileum, jejunum except proximal 15 cm and greater omentum). Postoperative complications occurred in eight patients were: scrotal hematoma, deep mesh infection, seroma and hydrocele. There were three postoperative deaths: 12 hours, 17 and 42 days after the surgery because ischemic enteritis, cerebrovascular stroke and heart failure, respectively. Conclusion: Our strategy consisting of modified Rives technique performed through direct inguinal approach with or without additional procedures to reduce the volume of organs returned to the abdomen or to enlarge the primary abdominal cavity can be a good solution for giant inguinoscrotal hernias. Procedure is followed by the risk of deadly complications and requires trained team in intesive care unit.